The Measurement of Recovery Time in Patients Receiving Hemodialysis for End-Stage Renal Disease - Quach, Kevin (My University, 2015)
Hemodialysis induces various symptoms in many patients. However, the type of dialysis symptoms induced and how they contribute to recovery time remains unclear. This study aims to understand patient experiences reporting dialysis recovery time and associated symptoms using three separate novel instruments developed for this study. We conducted a 13-week prospective cohort study in prevalent in-center hemodialysis patients and measured their recovery time using three instruments. Instrument A inquired how long it took to recover from the last dialysis treatment. Instrument B inquired recovery time from last treatment for each of 10 specified symptoms and Instrument C included symptom severity to Instrument B. Each instrument was used for each dialysis treatment for one week. We compared patient response and distribution of recovery time found with each instrument using mixed-effects logistic regression models. 118 participants were recruited from two centres of which 914 (86%) of 1062 expected responses were completed. Recovery time using instrument A resulted in more participants identifying some recovery time from dialysis (83 to 86%) as compared with Instrument B (66 to 80%, p = 0.001) and Instrument C (69 to 73%, p <0.001). The third visit of the week was associated with fewer patients reporting recovery time (p = 0.036). However, Instrument B (p = 0.016) and Instrument C (p < 0.001) showed a longer recovery time compared to the distribution of recovery time of Instrument A. Lack of energy was the most common symptom following dialysis (69 to 77% of all patients). Recovery time with Instrument A was a significant predictor of kidney-specific component scores and mental component score as measured by the Kidney Disease Quality of Life-36 instrument. Recovery time is complex, and includes different symptoms that vary in duration. Attempts to reduce recovery time may impact specific symptoms differentially.
Keywords: Nephrology; Quality of life; Dialysis; Measurement